The unstoppable sales machine : how to connect, convert, and close new customers - Casemore, Shawn (Productivity Press, 2022)
You're in big trouble if you rely on having "feet on the street" to generate new sales. Selling in today's economy has forever changed. Buyers today are more challenging to reach and offer less of their time to anyone in sales. So it's time to rethink how we generate sales to create a sustainable model that produces consistent results. This book addresses the shifts sales professionals, and their organizations need to make in introducing modern sales strategies. It provides insights and proven strategies for business owners, sales executives, leaders, and professionals -- anyone who desires to create a rapid and sustained increase in their sales without investing significant time or money. In a comprehensive review of the author's work with global companies, Casemore introduces a model for "Unstoppable Selling" -- capturing the strategies and tactics of how top-performing companies have continued to sell more each year, all while increasing the predictability of their sales growth. This book contains powerful models, tools, and resources, including the Hybrid Sales Funnel, Rocket Fuel Referral Process, and the Market Maximizer. In addition, the book demonstrates how you can quickly establish your Unstoppable Sales Machine regardless of the size or sector of your company. Introducing your own unstoppable sales machine will not require you to hire a bunch of experts or more employees. This book accepts you where you are and then walks you through the steps to quickly introduce and launch your very own machine. You'll find all the advice, guidance, case studies, and worksheets in this one convenient book ready for you to implement. If you intend to scale your business or want more freedom from the daily rollercoaster of your current sales strategy, this is the book for you. Selling is a noble profession and the heart and soul of every business -- Yet the continued evolution of today's customers, how they engage, select, and buy products and services, requires we rethink how we approach selling. In this book, Casemore shows you how to become an expert at sales while having the freedom and comfort of knowing that your machine will never let you down.